Method for preparing Pr < 3 + >: Y1. 8La0. 2O3 transparent ceramic through spark plasma sintering

By using BN-sprayed Ta foil to wrap the powder and adding LiF during SPS sintering, the problem of transparent ceramics being susceptible to carbon contamination is solved, which improves the transmittance and simplifies the preparation process.

CN119797918APending Publication Date: 2025-04-11NANCHANG HANGKONG UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510023084.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The process of SPS preparing transparent ceramics is prone to carbon pollution, resulting in a decrease in transmittance.

Method used

The powder to be sintered is wrapped with BN-sprayed Ta foil inside the graphite mold, and a certain amount of LiF is added before the transparent ceramic powder is sintered to reduce carbon pollution.

Benefits of technology

It effectively reduces carbon pollution in the SPS sintering process, significantly improves the transmittance of Pr3+:Y1.8La0.2O3 transparent ceramics, and reduces the sintering temperature and insulation time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797918A_ABST
    Figure CN119797918A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing Pr < 3 + >: Y1. 8La0. 2O3 transparent ceramic by spark plasma sintering. The method comprises the following steps: (1) preparing Pr < 3 + >: Y1. 8La0. 2O3 transparent ceramic powder by using a precipitation method; (2) adding a proper amount of LiF into the prepared Pr < 3 + >: Y1. 8La0. 2O3 transparent ceramic powder, pouring into absolute ethyl alcohol, stirring and mixing, and performing suction filtration and drying to obtain powder required by sintering; (3) wrapping the powder prepared in the step (2) with Ta foil sprayed with BN before sintering, and then performing SPS sintering; and (4) grinding and polishing the obtained block by using abrasive paper until the thickness is 1mm-1.1 mm, so as to obtain the Pr < 3 + >: Y1. 8La0. 2O3 transparent ceramic. According to the method, the Ta foil sprayed with BN is used for wrapping the powder to be sintered in the graphite mold, and a certain amount of LiF is added before the transparent ceramic powder is sintered, so that carbon pollution in the SPS sintering process can be effectively reduced, and the transmittance of the Pr < 3 + >: Y1. 8La0. 2O3 transparent ceramic is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of transparent ceramics and preparation technology, and relates to a method for preparing Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic method. Background Art

[0002] Yttria transparent ceramics have the advantages of low phonon energy, low thermal expansion coefficient and high thermal conductivity. 3+ , Yb 3+ 、Nd 3+ It is one of the ideal matrix materials for lasers, etc., and shows great prospects in many fields such as high-power lasers and scintillation materials. 3+ As one of the effective ways to emit red laser, the excitation of can effectively reduce afterglow, increase the probability of radiation transition and fully improve the luminous efficiency, and has been widely studied.

[0003] SPS is a new type of sintering method that has emerged in the field of materials in recent years. It provides a method for quickly sintering ceramic powders or nanomaterials to high density at a relatively low temperature and in a short time. However, since the sample is placed in a carbon-rich atmosphere during the sintering process, the sample is very susceptible to carbon contamination. Especially for transparent ceramics, carbon contamination has a huge impact on its transmittance. For example, the research of Naum Frage et al. shows that adding a certain amount of LiF can reduce the carbon contamination and sintering temperature of YAG transparent ceramics. When the wavelength of light is 1μm, adding a certain amount of LiF increases the transmittance of transparent ceramics by more than 40% compared with that without adding LiF. (Frage N, Kalabukhov S, Sverdlov N, et al. Densification of transparent yttrium aluminum garnet (YAG) by SPS processing [J]. Journal of the European Ceramic Society, 2010, 30 (16): 3331-3337.)

[0004] In summary, SPS has the advantages of quickly sintering samples to high density and can reduce the sintering temperature and time of samples. This is an ideal sintering method for transparent ceramics that need to be sintered at high temperature and high pressure. However, since it is very easy to cause carbon contamination of samples, it often fails to achieve the ideal effect in the sintering of transparent ceramics. How to reduce the carbon contamination caused by SPS has become a key issue. Summary of the invention

[0005] The present invention mainly solves the problem of carbon pollution caused by SPS in the process of preparing transparent ceramics, which greatly reduces the transmittance of transparent ceramics, and provides a method for preparing Pr 3+ :Y 1.8 La 0.2 The method of using BN-sprayed Ta foil to wrap the powder to be sintered inside the graphite mold and adding a certain amount of LiF before sintering the transparent ceramic powder can effectively reduce the carbon pollution in the SPS sintering process and greatly improve the Pr 3+ :Y 1.8 La 0.2 Transmittance of O3 transparent ceramics.

[0006] The present invention is achieved through the following technical solutions.

[0007] A method for preparing Pr by spark plasma sintering 3+ :Y 1.8 La 0.2 The method of O3 transparent ceramic comprises the following steps:

[0008] (1) Preparation of Pr using precipitation method 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder;

[0009] (2) In the prepared Pr 3+ :Y 1.8 La 0.2 Add an appropriate amount of LiF to the O3 transparent ceramic powder, pour it into anhydrous ethanol and stir and mix, and then filter and dry to obtain the powder required for sintering;

[0010] (3) Before sintering, the powder obtained in step (2) is wrapped with Ta foil sprayed with BN to isolate the powder from the graphite mold, and then SPS sintering is performed; before wrapping the powder with Ta foil, the side of the Ta foil in contact with the powder is evenly sprayed with BN spray;

[0011] (4) The obtained block was ground and polished with sandpaper to a thickness of 1 mm to 1.1 mm to obtain Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic.

[0012] Furthermore, in step (1), Pr 3+ :Y 1.8 La 0.2 The chemical formula of O3 transparent ceramic powder is Y 1.79 La 0.2 Pr 0.01 O3.

[0013] Further, step (1) is specifically as follows: dissolving the raw material powder in a calculated ratio in nitric acid according to the chemical formula to prepare a titration solution with a concentration of 1 mol / L, titrating it into a precipitant with a concentration of 0.1 mol / L composed of NH4OH and NH4HCO3, and stirring continuously. The precipitate is the precursor, and then calcining the precursor at 900°C for 2h to obtain Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder.

[0014] Further, in step (2), Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder and 0.3wt% LiF were added to anhydrous ethanol and stirred for 6 hours to make LiF and Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder is evenly mixed.

[0015] Furthermore, in step (3), the thickness of the Ta foil is 0.025 mm.

[0016] Furthermore, in step (3), the process of loading the powder obtained in step (2) into the mold before sintering is as follows: first, one side of the powder wrapped in Ta foil is evenly sprayed with BN spray, then the inner wall and bottom of the graphite mold are wrapped with Ta foil sprayed with BN, and then the powder obtained in step (2) is loaded, and finally the part of the powder that contacts the upper pressure head is wrapped with Ta foil sprayed with BN.

[0017] Compared with the prior art, the advantages of the present invention are: the present invention uses Ta foil sprayed with BN to wrap the powder to be sintered inside the graphite mold, and adds a certain amount of LiF before sintering the transparent ceramic powder, which can effectively reduce the carbon pollution in the SPS sintering process and greatly improve the Pr 3+ :Y 1.8 La 0.2 The transmittance of O3 transparent ceramics is improved, and based on the advantages of SPS and LiF, the sintering temperature and holding time are reduced, making the preparation of transparent ceramics simpler. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the Pr of Example 1 3+ :Y 1.8 La 0.2 Preparation flow chart of O3 transparent ceramics;

[0019] Figure 2 It is a cross-sectional view of the graphite mold of embodiments 1, 2 and 3;

[0020] Figure 3 Pr of Example 13+ :Y 1.8 La 0.2 X-ray diffraction pattern of O3 transparent ceramics;

[0021] Figure 4 Pr of Embodiments 1, 2 and 3 3+ :Y 1.8 La 0.2 Photos of O3 transparent ceramic after polishing;

[0022] Figure 5 Pr of Example 1 3+ :Y 1.8 La 0.2 Microstructure photos of the surface of O3 transparent ceramic after polishing and acid corrosion;

[0023] Figure 6 Pr of Embodiments 1, 2 and 3 3+ :Y 1.8 La 0.2 Transmittance curve of O3 transparent ceramic after polishing.

[0024] In the figure: 1. Ta foil, 2. BN, 3. graphite paper, 4. powder. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0026] A method for preparing Pr by spark plasma sintering 3+ :Y 1.8 La 0.2 The method of O3 transparent ceramic comprises the following steps:

[0027] (1) Preparation of Pr using precipitation method 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder;

[0028] (2) In the prepared Pr 3+ :Y 1.8 La 0.2 Add an appropriate amount of LiF to the O3 transparent ceramic powder, pour it into anhydrous ethanol and stir and mix, and then filter and dry to obtain the powder required for sintering;

[0029] (3) Before sintering, the powder obtained in step (2) is wrapped with Ta foil sprayed with BN to isolate the powder from the graphite mold, and then pressed to obtain a graphite mold with a ceramic blank in the middle, which is then placed in SPS for sintering to obtain Pr 3+ :Y 1.8 La 0.2O3 transparent ceramic block; before using Ta foil to wrap the powder, spray BN spray evenly on the side of the Ta foil that contacts the powder;

[0030] (4) The obtained block was ground and polished with sandpaper to a thickness of 1 mm to 1.1 mm to obtain Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic.

[0031] Furthermore, in step (1), Pr 3+ :Y 1.8 La 0.2 The chemical formula of O3 transparent ceramic powder is Y 1.79 La 0.2 Pr 0.01 O3.

[0032] Further, step (1) is specifically as follows: dissolving the raw material powder in a calculated ratio in nitric acid according to the chemical formula to prepare a titration solution with a concentration of 1 mol / L, titrating it into a precipitant with a concentration of 0.1 mol / L composed of NH4OH and NH4HCO3, and stirring continuously. The precipitate is the precursor, and then calcining the precursor at 900°C for 2h to obtain Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder.

[0033] Further, in step (2), Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder and 0.3wt% LiF were added to anhydrous ethanol and stirred for 6 hours to make LiF and Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder is evenly mixed.

[0034] Furthermore, in step (3), the thickness of the Ta foil is 0.025 mm.

[0035] Furthermore, in step (3), the process of loading the powder obtained in step (2) into the mold before sintering is as follows: first, one side of the Ta foil wrapped powder is evenly sprayed with BN spray, then the inner wall and bottom of the graphite mold are wrapped with Ta foil sprayed with BN, and then the powder obtained in step (2) is loaded into the graphite mold, and finally the part of the powder that contacts the upper pressure head is wrapped with Ta foil sprayed with BN.

[0036] Embodiment 1

[0037] A method for preparing Pr by spark plasma sintering 3+ :Y 1.8 La 0.2The method of O3 transparent ceramic comprises the following steps:

[0038] (1) Preparation of Pr using precipitation method 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder; specifically: according to the chemical formula, the raw material powder (raw material powder is Y2O3, La2O3, Pr6O 11 ) was dissolved in nitric acid to prepare a titration solution with a concentration of 1 mol / L, which was titrated into a precipitant composed of NH4OH and NH4HCO3 with a concentration of 0.1 mol / L, and stirred continuously. The precipitate was the precursor, and then the precursor was calcined at 900 ° C for 2 h to obtain Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder.

[0039] (2) In the prepared Pr 3+ :Y 1.8 La 0.2 Add an appropriate amount of 0.3wt% LiF to the O3 transparent ceramic powder, pour it into anhydrous ethanol and stir and mix, continue stirring for 6 hours, and obtain the powder required for sintering after suction filtration and drying;

[0040] (3) Before sintering, the powder obtained in step (2) is wrapped with Ta foil sprayed with BN; the specific process is: first, one side of the Ta foil wrapped powder is evenly sprayed with BN spray, then the inner wall and bottom of the graphite mold are wrapped with Ta foil sprayed with BN, and then the powder obtained in step (2) is loaded into the graphite mold, and finally the part of the powder in contact with the upper pressure head is wrapped with Ta foil sprayed with BN;

[0041] The thickness of the Ta foil is 0.025 mm, so that the powder and the graphite mold can be isolated. After pressing and molding, a graphite mold with a ceramic blank in the middle is obtained. The pressing process is to apply pressure to the upper and lower pressure heads of the graphite mold, the pressure is 15 MPa, and the pressure holding time is 10 minutes;

[0042] Then put it into SPS for sintering to obtain Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic block; the sintering process is to reach 1100℃ at a heating rate of 100℃ / min, the sintering pressure reaches 80MPa, and then heat to 1550℃ at a heating rate of 20℃ / min, release the pressure after keeping warm for 20min, and cool down with water, wherein the initial pressure is 15Mpa.

[0043] (4) The obtained block was ground and polished with sandpaper to a thickness of 1 mm to 1.1 mm to obtain Pr 3+ :Y1.8 La 0.2 O3 transparent ceramic.

[0044] Embodiment 2

[0045] The only difference between Example 2 and Example 1 is that the Ta foil is not sprayed with BN spray, and the other steps are the same.

[0046] Embodiment 3

[0047] The only difference between Example 3 and Example 1 is that the Ta foil sprayed with BN is replaced by graphite paper sprayed with BN, and the other steps are the same.

[0048] Figure 2 (a) is a cross-sectional view of the graphite mold of Example 1. The polished transparent ceramic obtained in Example 1 was subjected to X-ray diffraction and transmittance tests. Figure 3 and Figure 6 As shown in (a), the transparent ceramic is then acid-etched and then subjected to microstructural analysis. Figure 5 shown.

[0049] Figure 2 (b) is a cross-sectional view of the graphite mold of Example 2, and the Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic. Polished Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramics can see the text below the sample, and the transmittance at 800nm ​​is 41.19%.

[0050] Figure 2 (c) is a cross-sectional view of the graphite mold of Example 3, and the Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic. Polished Pr 3+ :Y 1.8 La 0.2 The middle part of the O3 transparent ceramic is black, and it is difficult to see the text below the sample. The transmittance at 800nm ​​is 10.16%.

[0051] Figure 3 Pr prepared in Example 1 3+ :Y 1.8 La 0.2 The X-ray diffraction spectrum of O3 transparent ceramic after polishing shows that the preparation of Pr 3+ :Y 1.8 La 0.2The peak corresponding to the O3 transparent ceramics coincides with the peak of the Y2O3 standard PDF card, and no second phase appears.

[0052] Figure 4 Pr prepared in Examples 1, 2 and 3 3+ :Y 1.8 La 0.2 The photo of O3 transparent ceramic after polishing. Figure 2 (a) The transparent ceramics prepared by the method are compared with Figure 2 (b) and Figure 2 (c) Transparent ceramics have low carbon contamination and higher transmittance, allowing the text on paper to be clearly seen.

[0053] Figure 5 Pr prepared in Example 1 3+ :Y 1.8 La 0.2 The microstructure of the surface of the O3 transparent ceramic after polishing and acid corrosion; As can be seen from the figure, the Pr prepared in Example 1 3+ :Y 1.8 La 0.2 The average grain size of O3 transparent ceramics is 50μm to 100μm, and the structure is dense.

[0054] Figure 6 Pr prepared in Examples 1, 2 and 3 3+ :Y 1.8 La 0.2 Transmittance curve of O3 transparent ceramic after polishing: As can be seen from the figure, the use Figure 2 (a) The transparent ceramics prepared by the method are compared with Figure 2 (b) and Figure 2 (c) The transmittance at 800 nm is even higher, at 50.07%, indicating good optical performance.

[0055] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. Preparation of Pr by spark plasma sintering 3+ :Y 1.8 La 0.2 The method of O3 transparent ceramics is characterized in that, The steps include: (1) Preparation of Pr using precipitation method 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder; (2) In the prepared Pr 3+ :Y 1.8 La 0.2 Add an appropriate amount of LiF to the O3 transparent ceramic powder, pour it into anhydrous ethanol and stir and mix, and then filter and dry to obtain the powder required for sintering; (3) Before sintering, the powder obtained in step (2) is wrapped with Ta foil sprayed with BN, and then SPS sintering is performed; before wrapping the powder with Ta foil, the side of the Ta foil in contact with the powder is evenly sprayed with BN spray; (4) The obtained block is ground and polished with sandpaper to obtain Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic.

2. The method for preparing Pr by spark plasma sintering according to claim 1 3+ :Y 1.8 La 0.2 The method of O3 transparent ceramics is characterized in that, In step (1), Pr 3+ :Y 1.8 La 0.2 The chemical formula of O3 transparent ceramic powder is Y 1.79 La 0.2 Pr 0.01 O3.

3. The method for preparing Pr by spark plasma sintering according to claim 1 3+ :Y 1.8 La 0.2 The method of O3 transparent ceramics is characterized in that, Step (1) is specifically as follows: dissolving the raw material powder in a calculated ratio in nitric acid according to the chemical formula to prepare a titration solution with a concentration of 1 mol / L, titrating the solution into a precipitant with a concentration of 0.1 mol / L composed of NH4OH and NH4HCO3, and stirring continuously. The precipitate is the precursor, and then calcining the precursor at 900°C for 2h to obtain Pr 3+ :Y 1.8 La 0.2 O3 transparent ceramic powder.

4. The method for preparing Pr by spark plasma sintering according to claim 1 3+ :Y 1.8 La 0.2 The method of O3 transparent ceramics is characterized in that, In step (2), Pr3+:Y1.8La0.2O3 transparent ceramic powder and 0.3wt% LiF are added to anhydrous ethanol and stirred for 6 hours to uniformly mix LiF and Pr3+:Y1.8La0.2O3 transparent ceramic powder.

5. The method for preparing Pr by spark plasma sintering according to claim 1 3+ :Y 1.8 La 0.2 The method of O3 transparent ceramics is characterized in that, In step (3), the thickness of the Ta foil is 0.025 mm.

6. The method for preparing Pr by spark plasma sintering according to claim 1 3+ :Y 1.8 La 0.2 The method of O3 transparent ceramics is characterized in that, In step (3), the process of loading the powder obtained in step (2) into the mold before sintering is as follows: first, one side of the Ta foil wrapped powder is evenly sprayed with BN spray, then the inner wall and bottom of the graphite mold are wrapped with Ta foil sprayed with BN, and then the powder obtained in step (2) is loaded, and finally the part of the powder that contacts the upper pressure head is wrapped with Ta foil sprayed with BN.

Citation Information

Patent Citations

  • Preparation method of yttria-base transparent ceramic

    CN104557041A

  • Method for preparing aluminum oxynitride transparent ceramic

    CN107344854A

  • Simple and efficient hot pressed sintering preparation method of Ce: YAG transparent ceramic

    CN114621002A

  • Preparation method of yttrium oxide transparent ceramic

    CN118495949A